Actualización del sistema globalmente armonizado y residuos peligrosos en el instituto nacional de salud (2023)
This document presents the development and results obtained during the university internships carried out at the National Institute of Health (INS), specifically in the Microbiology Group. The INS is a public entity that is part of the Department of Science, Technology and Innovation and the Department of Health and Social Protection. Its main functions are to ensure public health surveillance and conduct research on health issues, among other related aspects. The institute is located in the district of Teusaquillo, in the city of Bogotá. During the internship, the main objective was to update the "Globally Harmonized System of Classification and Labeling of Chemicals (GHS)". The purpose of this initiative is to provide a standardized framework to ensure the proper identification, classification, labeling and communication of the risks associated with the use of chemicals.